232 The epithelial-to-mesenchymal transition (EMT) contributes to immunosuppression in breast carcinomas and regulates their response to immune checkpoint blockade. (10th December 2020) - Dongre, Anushka; Weinberg, Robert; Rashidian, Mohammad; Eaton, Elinor; Reinhardt, Ferenc; Thiru, Prat; Zagorulya, Maria; Nepal, Sunita; Banaz, Tuba; Martner, Anna; Spranger, Stefani
Abstract : Background: Immune checkpoint blockade (ICB) has generated some dramatic responses in certain types of human tumors, most notably, melanomas. However, the response of breast tumors has been largely limited. We have previously demonstrated that the residence of breast cancer cells in the epithelial or mesenchymal phenotypic states can itself be used as an important determinant of the success or failure of ICB. Specifically, we have shown that while epithelial tumors are sensitive to anti-CTLA4, mesenchymal tumors are highly resistant. Most strikingly, in tumors arising from a mixture of both cell types, a minority population (10%) of mesenchymal cells can cross-protect the vast majority (90%) of their epithelial neighbors from immune attack. 1 However, the mechanisms underlying such cross-protection remain elusive. This is particularly important as most human breast cancers contain minority populations of such mesenchymal cells which can protect the tumor as a whole from immune attack. Methods: Using a combination of transcriptomic and CRISPR/Cas9 approaches, we first identified that mesenchymal carcinoma cells express high levels of CD73, an ecto-enzyme that catalyzes the production of adenosine. Additionally, we used digital spatial profiling to determine whether CD73 expression differs across distinct epithelial and mesenchymal sectors in mixed tumors. Results: Abrogation of CD73 from mesenchymal carcinoma cells prevented the assembly of an immunosuppressive tumor microenvironment and resulted instead in increased numbers of tumor-infiltrating lymphocytes and cross-presenting dendritic cells. Most strikingly, abrogation of CD73 sensitized previously refractory mesenchymal tumors completely to ICB. In the context of mixed tumors comprised of both epithelial and mesenchymal carcinoma cells, gradients in expression of CD73 were observed corresponding to the epithelial or mesenchymal sectors of these mixed tumors. Importantly, mixed tumors in which the minority population of mesenchymal carcinoma cells lacked the expression of CD73, were also sensitized partially to ICB. Thus, these mesenchymal carcinoma cells knocked out for CD73 could no longer protect their epithelial neighbors from immune attack. Conclusions: Taken together, our work suggests that mesenchymal carcinoma cells exert immune-suppressive effects which are also prominent in heterogeneous tumors. Furthermore, targeting the adenosinergic signaling pathway in mesenchymal carcinoma cells can potentiate the efficacy of ICB. Reference: Dongre A, Rashidian M, Reinhardt F, Bagnato A, Keckesova Z, Ploegh HL, Weinberg RA, Epithelial-to-mesenchymal transition contributes to immunosuppression in breast carcinomas. Cancer Res 2017 Aug 1;77(15):3982–3989.